THE ROLE OF PSYCHOLOGISM IN THE DEVELOPMENT OF A LITERARY GENRE - Rajabov Akham Uktamovich; Jalilova Lola Jalilovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The given article deals with the role of psychologism in the development of literary genre. The internal and external components of psychologism are discussed. The case for the presence of psychological manifestations in literary works is analyzed. Psychologism is considered as a form of emphasizing humanism, high ideological and moral standards as well as a certain principle of organizing the elements of art in a specific unity.